Peningkatan Kemampuan Koneksi Matematis Mahasiswa Melalui Pembelajaran Matematika Kontekstual - Fitriana Yolanda; Putri Wahyuni (Universitas Muria Kudus, 2020)
The purpose of this study is to determine the improvement of students' mathematical connection abilities through contextual mathematics learning. This research was conducted on the fourth semester students of mathematics education study programs at the Riau Islamic University. This research is a quasi experiment design research. Determination of the sample is determined by saturation sampling and selection of the experimental class and the control class using simple random sampling. The research instrument was a student's mathematical connection ability test and data analysis using the Mann-Whitney test. The results showed that the average N-gain of mathematical connection ability of students who received contextual learning was 0.30, in the medium category, while the average N-gain of mathematical connection ability of students who obtained conventional learning by 0.19 was in the category low. The conclusion of the research is to increase the mathematical connection ability of students who get contextual learning better than students who get conventional learning